Descriptive temporal sensory properties and volatile composition of Pinot noir wines produced with contrasting alcoholic fermentation temperatures and cap management regimes - Stoffel, Emily S. (2024)
Pinot noir is rapidly becoming a winemaking staple in the Central Coast of California. Therefore, it is important to understand how factors such as fermentation temperature and cap management affect the chemical and sensory impact of such wines. Herein, Pinot noir wines were made with three contrasting alcoholic fermentation temperature regimes (Cold, Cold/Hot, Hot) and combined factorially with two cap management regimes (with or without punch downs). The impact of these factors on colour, aroma, and the temporal retronasal aroma and mouthfeel profile was assessed by a trained sensory panel (n = 13) using descriptive analysis (DA) and time-intensity (TI), respectively. Combining a hot fermentation temperature and no punch downs led to wines with higher colour saturation and purple hue. In contrast, wines fermented at cold fermentation temperatures with no punch downs showed reduction aromas. In terms of individual main effects, wines fermented at cold temperatures had more orthonasal aroma, while wines fermented at hot temperatures had higher astringency. To understand the relationship between selected volatile aromas and perceived sensory results, a partial least square regression (PLSR) was conducted. PLSR indicated that cold fermentation temperature wines with punch downs were associated with esters, including ethyl hexanoate and ethyl heptanoate, as well as β-damascenone, which aligned with sensory results. The effect of salivary flow rate on the temporal sensory profile post-expectoration was also analysed. Low salivary flow rate panellists perceived bothastringency and length significantly later and more intensely than high salivary flow rate panellists. However, the time of maximum intensity was perceived significantly later for high salivary flow rate panellists. Overall, fermentation temperature had a more significant impact on the sensory and volatile composition of Pinot noir wines than the cap management regime. However, cap management still appeared to affect sensory and volatile chemistry results through significant interactions. Therefore, the relationship between fermentation temperature and cap management was not straightforward from a volatile chemistry or sensory perspective. The importance of accounting for salivary flow rate in panellists when using time-based sensory analysis was also highlighted.